PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Safrida, Eli (Program Studi Akuntansi FPEB UPI, 2014)
The purpose of this study was to analyze the effect of profitability on dividend policy, to analyze the effect of the company's growth to dividend policy, to analyze the effect on the company's profitability and growth dividend policy.The object of research companies listed in Indonesia Stock Exchange the period 2008-2011. The number of samples is 26 companies, the samples were taken by using purposive sampling method. Tools of data analysis using linear regression.The results obtained from the analysis of the data is positive and significant effect of profitability on dividend policy, growth companies positive but not significant effect on dividend policy, profitability and corporate growth and a significant positive effect on dividendpolicy.